AN ANALYSIS OF TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION IN SECONDARY SCHOOL - Zaman, Yahya Badruz Zaman; Pradana, Dian Arief Pradana; Pambayun, Rizki Nurfida Pambayun (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was conducted to find out what strategies that teachers usefor teaching reading comprehension in MAN abc Banyuwangi. Thisresearch used descriptive qualitative method. In the implementation ofthis study the researcher conducted interviews and document analysis toobtained relevant data to answer the objectives of this research. Thisresearch was conducted at MAN abc Banyuwangi and two Englishteachers were selected as samples in this study. Based on the results of theinterview with two English teachers, the data obtained is the teachersusing different strategy in teaching reading comprehension. The firstteacher use Scaffolding strategy while the second teacher use peerteaching. Scaffolding strategy can develop ideas that students can read.Peer teaching can develop student’s mentality also readingcomprehension ability. These strategies should be selected on the basis oftheir suitability and effectiveness with the learning process so that theiruse will allow teachers to explore students' ideas and help them read in abetter way. Based on the interview analysis, the reason why the teacheruses this type of strategy in students' reading comprehension is becauseto make students understand the text and guide students to focus moreon the text.